Utopijna wizja wychowania pedagogiki serca Marii Łopatkowej w kontekście wartości czasów współczesnych - Piecuch, Ewelina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Maria Łopatowska has created a pedagogic trend named pedagogy of the heart, which was based on the author's vision of personal respect for children. Utopian, idealistic, leaving much to wish for concept of educating the young generation, encourages to reflect on the values of idealistic education and the realities posed by contemporary life. It is the expression of humanism on the position of the child in case of a change in his or her educational, family home and personal space. Pedagogy of the heart contains a timeless utopian vision of a clash of positive intentions with the limitations and imperfections of the world, which is ruled by consumerism, haste and constant change. Realistic look at the child as an entity that is not fully formed, remaining in constant development, which has its own strengths and weaknesses that are arising from the situations to which he or she got exposed, shows the vision of the trend’s author, as impossible to fulfill. M. Łopatkowa created pedagogy of the heart based on exactly those assumptions. Perspective inspired by humanism of the position of a child in the situation of contemporary times hides a time-less utopian vision of conflict of positive intentions and the limits and imperfections of the world ruled by consumerism, rush and constant change.
Keywords: Łopatkowa Maria; values; pedagogy of heart; utopia; upbringing; modernity; school; teacher; students